How Socio-Economic and Cultural Factors Shape Privacy in Ibadan's Public Housing Estates - Amao, Funmilayo Lanrewaju; Rahbarianyazd, Rokhsaneh; Odunjo, Oluronke Omolola (Alanya Üniversitesi, 2024)
This study investigates the socio-economic and cultural characteristics of residents in selected public housing estates in Ibadan, focusing on the privacy regulatory mechanisms they adopt. By employing a mixed-methods approach, the research involved administering questionnaires to 565 household heads and conducting in-depth interviews with eight key informants from neighbourhood associations. The findings indicate a significant majority (92.00%) of respondents have adopted privacy regulating mechanisms, with personal space and territorial behaviour being the most common. ANOVA results reveal a significant relationship between these mechanisms and the residents' socio-economic and cultural characteristics. Qualitative insights from key informants' interviews provided a nuanced understanding of residents' privacy needs, highlighting emotional and behavioural cues, as well as verbal and non-verbal data. The study concludes that privacy regulation in public housing varies across different estates and is influenced by nine socio-economic and cultural factors, offering guidance for sustainable housing design that considers contemporary urbanization's socio-economic impacts. These findings can inform architects and policymakers in creating housing designs that respect privacy and enhance the quality of life for residents.